Automated Trading System - Le, Duc (2009)
This is a final report which is part of the dissertation for the Master course Computation Finance. The title of this dissertation is “Automated Trading System”. As the name explains itself, this project is about building an automated trading system which employs the statistical arbitrage trading algorithm. In general, the project contains a mixture of computer science and quantitative finance. For the purpose of simplicity, the system is designed with a simple user interface and streamlined business logic compare to a real world commercial trading system. The purpose of building this system is to build a starting point so that having a profitable trading algorithm implemented into the system will increase the probability of having a profitable trading system. The build phase of the project utilises Visual C++ programming language within the .NET framework.